Preparation Procedure and Pharmacokinetic Study of Water-in-Oil Nanoemulsion of Panax Notoginseng Saponins for Improving the Oral Bioavailability - Liu, Zhidong; Zhang, Qian; Ding, Lingling; Li, Chunhua; Yin, Zhongpeng; Yan, Guoqiang; Pi, Jiaxin; Li, Jiawei; Li, Nan; Qi, Dongli (Current Drug Delivery, 2016)
Background: Due to the effects of gastric acid, glycosidase and intestinal flora in the gastrointestinal environment, panax notoginseng saponins (PNS) can easily be resolved and metabolized when it is administered orally, limiting its oral bioavailability. Methods: The formula of PNS nanoemulsion (PNS-N) was optimized using a pseudoternary phase diagram, and the PNS-N was prepared by high pressure homogenization. The type, particle size, polydispersity index (PDI), refractive index, pH and content of PNS-N were characterized. In vitro characteristics were investigated by drug release and physical stability. The pharmacokinetic properties of PNS-N were studied with rat intestine and SD rats. The optimized nanoemulsion formulation was Labrafil M 1944CS (58%), SP/EtOH (Km=1) (25%), solution of PNS (400mg/ml) (17%). Results: The results showed that the average particle size was (28.17±0.39) nm with PDI of 0.116±0.032, refractive index of 1.4491±0.0009 and pH of 4.58±0.03. In addition, the contents of R1, Rg1 and Rb1 were (4.64±0.21) mg/mL, (19.16±0.27) mg/mL and (11.77±0.08) mg/mL, respectively. The optimized PNS-N formulation exhibited a sustained drug release with good stability. PNS-N is still clear and transparent, without layering and precipitation after six months. In the study of absorption kinetics of PNS-N in rat intestine, the Papp of three main components of PNS-N increased 5 times than PNS solution (PNS-SOL) in rat intestine. And pharmacokinetic study in SD rats suggested a 2.58-fold increase of oral bioavailability compared with PNS-SOL. Conclusion: The PNS-N has increased the absolute availability of PNS obviously and nanoemulsion is a potential formulation to improve oral bioavailability for PNS.
Keywords: oral bioavailability